2021
DOI: 10.3390/app11020617
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Spatial-Frequency Domain Imaging for Estimating Optical Absorption and Scattering Properties of Two-Layered Horticultural Products

Abstract: Spatial-frequency domain imaging (SFDI) is a wide-field, noncontact, and label-free imaging modality that is currently being explored as a new means for estimating optical absorption and scattering properties of two-layered turbid materials. The accuracy of SFDI for optical property estimation, however, depends on light transfer model and inverse algorithm. This study was therefore aimed at providing theoretical analyses of the diffusion model and inverse algorithm through numerical simulation, so as to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, and surprisingly enough, the prediction of firmness parameters based on the absorption properties was far better than that based on the scattering properties. This unexpected outcome could be attributed to the fact that SFDI is limited to light penetration depth (2–3 mm) ( Lu and Lu, 2019 ; Hu et al, 2021 ), while the firmness measurement by the texture analyzer probed the flesh much deeper (8 mm). In addition, the wavelengths used in this study are near to the characteristic wavelengths with absorption peaks, while the scattering properties have no features in those wavelengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, and surprisingly enough, the prediction of firmness parameters based on the absorption properties was far better than that based on the scattering properties. This unexpected outcome could be attributed to the fact that SFDI is limited to light penetration depth (2–3 mm) ( Lu and Lu, 2019 ; Hu et al, 2021 ), while the firmness measurement by the texture analyzer probed the flesh much deeper (8 mm). In addition, the wavelengths used in this study are near to the characteristic wavelengths with absorption peaks, while the scattering properties have no features in those wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, four wavelengths of 460, 527, 630, and 710 nm are used. When spatial frequency of the structured illumination is 0.20 mm –1 , the light penetration depth within apple tissue is approaching 1 mm ( Hu et al, 2021 ). High-frequency illumination has a relatively shallow light penetration depth, which could be interpreted by the depth-varying feature ( Hayakawa et al, 2018 ; Lu and Lu, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…When the penetration depth is greater than the thickness of the skin layer (z > d), the flesh layer of the two mediums begins to show differences in the results of the light-medium interaction due to the different optical properties of the two mediums. According to the literature [14], it is known that the influence of the flesh layer optical properties changing on the total reflectance are far less than those of the skin layer optical properties changing. Assuming the second scattering and second absorption of light in the tissue are not considered, the amount of light energy loss in the skin layer of the two mediums is the same.…”
Section: Extraction Of Optical Properties Of Two-layer Tissuesmentioning
confidence: 99%
“…However, due to the singleness of the research object, the results obtained by such models cannot be widely used in the optical properties detection of various fruits. Hu et al [14] aggregated the optical properties of various fruits for MC simulations in order to study the effect of four parameters (the skin layer absorption coefficient µ a1 , the skin layer reduced scattering coefficient µ s1 , the flesh layer absorption coefficient µ a2 and the flesh layer reduced scattering coefficient µ s2 ) on the prediction of reflectance. They found that the sensitivity of µ a2 and µ s2 changes was very small and difficult to separate at all spatial frequencies.…”
Section: Introductionmentioning
confidence: 99%